Juvenile Delinquency in the United States and the United Kingdom
XX, 197 p.
Keywords: This volume about juvenile delinquency in the United States and United Kingdom includes a foreword, nine chapters organized in three parts, and an afterword. Chapters 1 and 2 in Part I describe juvenile delinquency in both countries and the urgency of the current crisis. Chapters 3 to 6 in Part II deal with the two nations' juvenile justice systems, focusing on structural and ideological obstacles preventing reform. Presented in the final chapters in Part III are suggestions for reform in school, and juvenile justice setting that recognize the importance of character in causing delinquency.